Supply Chain Structure, Nature of Financing, and the Determinants and Consequences of Supply Chain Disclosure - A Resource-Based View - Velayutham, Ajantha (Auckland University of Technology, 2025)
Supply chain disruptions, such as the Covid-19 pandemic, have exposed the growing risks faced by supply chains. This is emphasised by the increasing globalisation and liberalisation of the global economy. Such complexities and uncertainties have heightened the need for transparency to mitigate the growing supply chain risks. The purpose of this thesis is to identify the structure of supply chains and examine the effects on important areas of risk. This includes examining the nature of supply chain financing and the nature, reasons, and effects of supply chain disclosures by companies to mitigate such a risk. Firstly, motivated by the liquidity problems faced by supply chains because of recent disruptions, the thesis investigates the effect of supply chain dimensions on the capital structure of companies. Secondly, motivated by the lack of visibility and transparency in supply chains and emphasised by the effects of the Covid-19 pandemic, it examines the effect of supply chain structure on supply chain disclosures of companies (SCD). Thirdly, the thesis examines whether SCD reduces information asymmetry in capital markets by measuring its effects on the cost of equity and cost of debt. Based on an exploratory sequential design methodology, interviews were first conducted with industry leaders to understand the dynamics and dimensions of the supply chain. These interviews, along with previous literature, were used to identify the supply chain dimensions. Four dimensions were identified. These were: (i) customer base, (ii) operating portfolio, (iii) environmental and (iv) social. Secondly, archival data were used to examine the above stated objectives on a sample of companies listed on the United Kingdom (UK) FTSE All-Share index. The sample was limited to companies operating in the manufacturing, retail and primary industries because these industries have supply chain structures with identifiable supply chain dimensions. In total, the sample has 80 companies with available data for a four-year period surrounding the Covid-19 years (2018 – 2022, with 320 firm-year observations). The thesis uses the resource-based view (RBV) to identify and explain the dimensions of the supply chain, focussing on the four dimensions. The findings of the first part of the thesis revealed that the customer base dimension (measured via domestic sales) was positively and significantly associated with capital structure (book leverage). This finding suggests that a more domestic-oriented customer base will reduce the structural complexity of the supply chain and have a lower level of risk as opposed to those of global supply chains, and as a result be more favourable towards debt financing. Additional tests were performed to examine moderation effects of other variables and alternate measures of capital structure. The findings revealed some positive association with short-term debt financing. The inclination towards debt financing and short-term debt financing for supply chains could be explained by the nature of activities involved. Most of the supply chain activities are of an ongoing operational nature which is likely to be financed by debt financing arrangements rather than equity. Overall, the findings show that among the four supply chain dimensions the nature of the customer base is most likely to affect the financing of the supply chain. The second part of the thesis examined the effects of the supply chain dimensions on the extent of SCD. The findings show an increase in SCD from pre-Covid levels and that there has been greater emphasis on messages communicating the operational supply chain information in the post-Covid years. The main findings show that customer base and social dimensions have a negative and significant relationship with SCD. The former relationship is due to a more localised customer base, resulting in the reduced complexity of supply chain operations and consequentially less SCD. A reason for the latter could be that social dimensions are enhanced through long-term collaborations with suppliers and SCD can threaten these collaborations through the disclosure of socially sensitive information. On the other hand, environmental dimensions had a positive and significant effect on SCD. This is likely because of the increased public attention on climate-related issues and a growing trend towards regulatory requirements being imposed by policy makers. The third part of the thesis examined the effect of SCD on the cost of equity and cost of debt. A non-significant, positive relationship was found against the cost of equity. This is likely due to the lack of relevant disclosures such as supply chain KPIs in current corporate reporting. In comparison, a significantly negative association was found with the cost of debt. This is because supply chain operations are predominantly financed with short-term debt financing, and debt providers would gain more certainty about corporate activities with higher SCD. Additional tests were conducted on the effect of supply chain messages and the effects of Covid on the cost of equity and cost of debt. The findings remained unchanged. This thesis contributes to the nascent literature on supply chain accounting, especially in light of disruptions caused by the major supply chain disrupter, Covid-19. More specifically, the thesis constructs a framework identifying the dimensions of the supply chain and examining the effects of four of these dimensions on supply chain financing and SCD. It further constructs a comprehensive SCD index and operationalises the index by measuring the extent of SCD in annual reports. The thesis also examines the effects of SCD on the costs of financing. It creates an awareness among shareholders, managers and creditors of the importance of communicating companies’ supply chain information. It also provides implications for companies to further communicate disclosures on their supply chain. Given that the scope of the current study was limited to examining annual reports, future research could investigate the dissemination of SCD through the more active communication channels to understand the dynamic nature of SCD. For better generalisation of the results across countries, studies should also investigate SCD in cross-country settings.
Keywords: Supply chain management; supply chain structure; supply chain disclosure; disclosure index; resource-based view; business model reporting